A vacuolar membrane protein Vsb1p contributes to the vacuolar compartmentalization of basic amino acids in Schizosaccharomyces pombe. Issue 6 (15th March 2022) - Ohnishi, Shota; Kawano-Kawada, Miyuki; Yamamoto, Yusuke; Akiyama, Koichi; Sekito, Takayuki
ABSTRACT: Accumulation levels of Arg, Lys, and His in vacuoles of Schizosaccharomyces pombe cells were drastically decreased by the disruption of SPAC24H6.11c ( vsb1 + ) gene identified by a homology search with the VSB1 gene of Saccharomyces cerevisiae . The Vsb1p fused with green fluorescent protein particularly localized at vacuolar membranes in S. pombe cells. Overexpression of vsb1 + markedly increased vacuolar levels of basic amino acids; however, overexpression of the vsb1 D174A mutant did not affect the levels of these amino acids. These results suggest that the vsb1 + contributes to the accumulation of basic amino acids into the vacuoles of S. pombe, and the aspartate residue in the putative first transmembrane domain conserved among fungal homologs is crucial for the function of Vsb1p. Graphical Abstract: